Project-Based Learning to Enhanced Student’s Writing Narrative Text Ability - Chadafi, Muammar (JEET, Journal of English Education and Technology, 2024)
This research is focused on investigating the effectiveness of Project Based Learning towards students writing narrative text ability of third grade students of MTs Al-Ishlah Deket Lamongan. It is based on the analysis of the data gained from the students related to teaching writing. The researcher used a quantitative approach that began with the research problem and answered it by proving the hypothesis. For the experiment and population, the researcher chose a class with twenty third-grade students. This was an experimental class. The instrument used to collect data was then evaluated. The test was used to determine students’ competencies before and after the experiment. Two kinds of tests were administered to the students: pre-test and post-test. Before the items of the test were given to the students, the researcher conducted a try-out test to analyze the validity and reliability of each item. The result shows that the student’s score at the pre-test was 45,2, and after giving treatment, the researcher obtained a post-test score of 78,6. Then, the researcher analyzed the results using the t-test to answer the research problem. The researcher obtained a t-test result of the t-test that is 5,60. The values of the t-test analysis are presented in the table. The t-table shows that the level of significant 0,05 was 2,09, meaning that the value of 5,60 was higher than 2,09. In conclusion, this study shows the effectiveness of the PBL method in students’ writing narrative texts. The researcher concludes that students taught by Project Based Learning (Pub) method obtained higher scores on their narrative writing texts.